BUKA LUWUR TRADITION: PORTRAIT OF LIVING HADITH AT HAUL SUNAN KUDUS - Friyadi, Arif (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2022)
Living hadith is the response of certain Muslim communities in applying the words that come directly from the Prophet Muhammad. This response occurs both in the form of personal and community in interpreting certain hadiths. This research will discuss the tradition of Buka Luwur with portraits of living hadiths on the haul of Sunan Kudus. This library research uses interview techniques and field observations to observe the Buka Luwur phenomenon in the Haul Sunan Kudus Commemoration. This social phenomenon is categorized as living hadith because there are several indications, including; First, this tradition was inspired by the turn of the kiswah of the Kaaba. Second, this tradition is considered by the Kudus community as a tribute to the services of Islamic preachers in the holy city, namely Sayyid Ja'far Sadiq, Sunan Kudus. Third, this tradition is considered to be based on hadith. The existence of this tradition also means that Islam does not only come as an emphasis on sharia, but also accommodates local traditions. From this phenomenon emerged a strong Islamic motivation in the form of generosity and inner satisfaction with respect to the first Islamic propagator on the island of Java.[Living hadis merupakan respon komunitas muslim tertentu dalam mengaplikasikan sabda yang bersumber langsung dari Rasulullah. Respon ini terjadi baik dalam bentuk personal maupun komunitas dalam memaknai hadis tertentu. Living hadis dipandang sebagai akulturasi antara ajaran Islam dan fenomena masyarakat dalam budaya lokal. Salah satu living hadis yang berkembang dalam masyarakat Kudus sejak abad ke-16 adalah peringatan buka luwur Sayyid Ja’far Shadiq, Sunan Kudus. Tradisi ini diperingati oleh masyrakat Kudus sebagai haul Sunan Kudus yang jatuh pada tanggal 10 Sura (Muharram). Penelitian dilakukan dengan menggunakan metode penelitian pustaka dan penelitian lapangan di Desa Kauman, Kota Kudus yang menjadi central penyebaran Islam pada abad ke-16. Fenomena sosial ini dikategorikan sebagai living hadis karena ada beberapa indikasi, di antaranya adalah; 1. Tradisi ini terinspirasi dengan pergantian kiswah ka'bah. 2. Tradisi ini dianggap masyarakat Kudus sebagai penghormatan atas jasa para pendakwah Islam di Kota kudus yaitu Sayyid Ja'far Shadiq, Sunan Kudus. 3. Tradisi ini dianggap berlandaskan hadis. Adanya tradisi ini juga berarti Islam tidak hanya datang sebagai penekanan syariat saja, namun juga mengakomodir tradisi lokal. Dari fenomena ini muncul motivasi keislaman yang kuat berupa kedermawanan dan kepuasan batin akan penghormatan kepada tokoh penyebar Islam pertama di pulau Jawa.]